ANALISIS KUALITAS GREYWATER PADA SISTEM DRAINASE DI HILIR TEPI SUNGAI CITARUM - Destari Anwariani; Rositayanti Hadisoebroto; Diana Irvindiaty Hendrawan (ITB Journal Publisher, LPPM ITB, 2020)
Abstract. Greywater generated from household activities in the riverbanks settlement is flowed directly into the drainage system. This research was conducted to analyze the level of pollution due to greywater flowed into drainage system in Citarum riverbanks, Kabupaten Karawang. Research was carried out on the drainage channel around settlements in 6 villages. The parameters analyzed were TSS, COD, BOD, Oil and Grease compared to the standard Minister of Environment Regulation No.68 of 2016. The TSS parameters was 11-292 mg/L, COD 28.8-441.6 mg/L, BOD 18.01-298.36 mg/L, Oil and Grease 1.9-13 mg/L. Parameter of TSS at all sampling points were exceed the quality standard, while parameters of COD and BOD were exceed in the 4 villages. Parameter of Oil and Grease at all points was above the quality standard in February, while in April, it was below the quality standard. High pollution on drainage system could be caused by the entry of greywater into the drainage channel that would contribute to pollute the Citarum River. This was occurs due to low level of knowledge and awareness in communities about pollution in the riverbanks and that there was not a proper treatment of greywater, whether in scale of household nor communal. Keywords: greywater, drainage system, Citarum River, riverbank, water quality